2013
DOI: 10.1002/pc.22793
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of thermoplastic polyurethane/graphene oxide composite scaffolds by thermally induced phase separation

Abstract: In this study, biomedical thermoplastic polyurethane/ graphene oxide (TPU/GO) composite scaffolds were successfully prepared using the thermally induced phase separation (TIPS) technique. The microstructure, morphology, and thermal and mechanical properties of the scaffolds were characterized by Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, scanning electron microscopy (SEM), differential scanning calorimetry (DSC), thermal gravimetric analysis (TGA), and compression tests. Furthermore, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 46 publications
4
32
0
Order By: Relevance
“…However, the increase of graphene loading led to wider and shallower endothermic curves and the melting enthalpy of the conductive foam with 3 wt% loading dropped to only 3.383 J g À1 , which might be due to the fact that the addition of graphene inhibited the crystallization of the TPU hard segments, leading to the decrease in the crystalline size of TPU molecules. 28,[47][48][49] As for the influence of graphene on the T g of CPC foams, it can be seen that the T g decreases with increasing graphene content, Fig. 3(b).…”
Section: Differential Scanning Calorimetry Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…However, the increase of graphene loading led to wider and shallower endothermic curves and the melting enthalpy of the conductive foam with 3 wt% loading dropped to only 3.383 J g À1 , which might be due to the fact that the addition of graphene inhibited the crystallization of the TPU hard segments, leading to the decrease in the crystalline size of TPU molecules. 28,[47][48][49] As for the influence of graphene on the T g of CPC foams, it can be seen that the T g decreases with increasing graphene content, Fig. 3(b).…”
Section: Differential Scanning Calorimetry Analysismentioning
confidence: 99%
“…23 Meanwhile, lightweight and high compressibility are of great importance for piezoresistive sensors to satisfy different practical demands. Due to the merits of lightweight, large specific surface area and high porosity, porous polymer foams have been widely used in many fields, including electromagnetic interference (EMI) shielding, [24][25][26][27] biological scaffolds [28][29][30][31] and super adsorbents. [32][33][34] As for the CPC based piezoresistive sensors, the introduction of a three-dimensional porous structure must be an effective strategy for achieving promising piezoresistive performance for widespread applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,30,31 The in vitro cytotoxicity of other carbon nanomaterials-reinforced PPF nanocomposites (MWCNTs, SWGONRs, MWGONRs, and GONPs) and inorganic nanomaterials-reinforced PPF nanocomposites (WSNTs and MSNPs) has not been reported. Cytocompatibility of some of these nanomaterials incorporated into other polymer nanocomposites such as PLGA (nonporous CNT/ PLGA 32 and porous GONP/PLGA 33 ), and PU (porous GONP/ PU scaffolds 34 ) has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…MG‐63 cells were seeded on the samples at an initial density of 1 × 10 5 to study the cytocompatibility and morphology, and then we observed the morphology of the cells by SEM after culturing for 1 and 5 d. Previous studies had reported that the addition of GO on the biopolymer matrix could enhance cell attachment and proliferation via a large number of hydrophilic groups on the surface . As depicted in Figure 9 , the majority of cells are spherical at the first day on bare PEEK; however, on the sulfonate PEEK group, lamellipodia can be observed clearly.…”
Section: Resultsmentioning
confidence: 99%